정상인에서 각막 생체역학인자가 파스칼안압계를 이용한 안구박동크기에 미치는 영향 - 권한조(Han Jo Kwon), 이지웅(Ji Woong Lee), 신종훈(Jong Hun Shin) (Daihan angwa haghoi jabji, 2015)
목적: 정상인에서 각막 생체역학인자가 파스칼안압계로 측정한 안구박동크기에 영향을 미치는지에 대하여 조사하였다. 대상과 방법: 2014년 1월부터 7월 안과 외래를 방문한 정상인들을 대상으로 파스칼안압계로 안구박동크기를 측정하고 안구반응분석기를 사용하여 각막이력(corneal hysteresis, CH), 각막저항인자(corneal resistance factor, CRF)를 측정하고, 골드만안압, 구면렌즈대응치, 안축장 및 중심각막두께를 측정하였다. 안구박동크기에 영향을 미치는 각막 역학인자 및 다른 안 인자들 간에 관계를 조사하기위해 단일 및 다중 선형회귀분석을 시행하였다. 결과: 평균 안구박동크기는 2.90 ± 1.04 mmHg, 평균 각막이력 및 각막저항인자는 각각 10.44 ± 1.96 mmHg, 11.03 ± 2.21 mmHg였다. 단일회귀분석에서 안구박동크기에 영향을 미치는 인자는 각막저항인자(β=0.280, p=0.049), 골드만안압(β=0.293, p=0.039), 구면렌즈대응치(β=0.283, p=0.047)로 조사되었지만 다중회귀분석에서는 오직 각막저항인자(β=0.686, p=0.042)만 관련이 있었다. 결론: 안관류압을 반영하는 안구박동크기와 각막의 탄성도를 반영하는 각막저항인자가 양의 상관관계를 가지는 것으로 나타났다. 두인자 간의 관련성은 향후 녹내장에서 안관류압의 변화에 대한 각막 생체역학인자의 영향을 분석하는 데 의미가 있을 것으로 사료된다. Purpose: To investigate the influence of corneal biomechanical factors on ocular pulse amplitude measured using dynamic contour tonometry in normal subjects. Methods: The study population consisted of normal subjects who visited the outpatient clinic from January, 2014 to July, 2014. Ocular pulse amplitude was measured using dynamic contour tonometry and corneal hysteresis (CH) and corneal resistance factor (CRF) were measured using an ocular response analyzer. We applied univariate and multivariate linear regressions to investigate the relationship between ocular pulse amplitude and corneal biomechanical factors and other ocular factors. Results: Fifty eyes of 50 patients (average age 52.8 ± 17.2 years) were examined. The average ocular pulse amplitude was 2.90 ± 1.04 mm Hg and the CH and CRF were 10.44 ± 1.96 mm Hg and 11.03 ± 2.21 mm Hg, respectively. In univariate linear regression, factors influencing ocular pulse amplitude were ocular pressure based on CRF (β = 0.280, p = 0.049), Goldmann applanation tonometry (β = 0.293, p = 0.039), and spherical equivalent (β = 0.283, p = 0.047), while in multivariate linear regression the only factor influencing ocular pulse amplitude was CRF (β = 0.686, p = 0.042). Conclusions: A positive correlation between ocular pulse amplitude reflecting ocular perfusion pressure and CRF reflecting corneal elasticity was observed. Correlations between the 2 factors will be an important aspect in future studies regarding the influences of corneal biomechanical factors on ocular perfusion pressure in glaucoma patients. KCI Citation Count: 0